The Kupyna hash function cryptanalysis with Merkle Trees Signature schemes - Kachko, O.; Televnyi, D. (Radiotekhnika, 2018)
The paper is devoted to the security analysis of the Kupyna (DSTU 7564:2014) hash function applied to Merkle tree signature schemes. The paper lists possible attacks on the hash, and their application for signature schemes. The results show expediency of using the Kypuna hash in Merkel schemes based on the performance, security levels and strength against known cryptanalytic attacks